If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3 + 3m) = 3(3m + 3) (3 * 6 + 3m * 6) = 3(3m + 3) (18 + 18m) = 3(3m + 3) Reorder the terms: 18 + 18m = 3(3 + 3m) 18 + 18m = (3 * 3 + 3m * 3) 18 + 18m = (9 + 9m) Solving 18 + 18m = 9 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 18 + 18m + -9m = 9 + 9m + -9m Combine like terms: 18m + -9m = 9m 18 + 9m = 9 + 9m + -9m Combine like terms: 9m + -9m = 0 18 + 9m = 9 + 0 18 + 9m = 9 Add '-18' to each side of the equation. 18 + -18 + 9m = 9 + -18 Combine like terms: 18 + -18 = 0 0 + 9m = 9 + -18 9m = 9 + -18 Combine like terms: 9 + -18 = -9 9m = -9 Divide each side by '9'. m = -1 Simplifying m = -1
| x^2-8x=-102 | | 6b+9=5b+17 | | 2.5(6x-4)=10+(1.5+0.5x) | | -7+13=4+n | | (0-6)(2x+1)=0 | | 10a-3=6a+33 | | 16=2(x-1)-6 | | 5a^2-9ab+8a= | | .30x+.50= | | -4.5=5x-x-x | | .30x+.5= | | -10(s+4)=-62 | | 2x+2=11x-70 | | 32+2+2=3.2 | | 2(f-1)=-4 | | x+2-3x=-8 | | 12y^6-16y5/4y^2 | | 11y+6=10y+8 | | 6x+4+4x+8=px+3 | | (3b+4b)(b-3)= | | 3(t+3)=-8 | | .30x+.05= | | 3-x=-2x-7 | | -48+n=14 | | 5(5c-1)-2=23c+5 | | -8y+4= | | (3/4)(7/6) | | 100+46+x=180 | | 99+43+x=180 | | 98+17+x=180 | | 2(5u)= | | 21k^2-34k+8=0 |